Mangosteen nutritional value and useful properties (Eurasian Journal of Research, Development and Innovation, 2022)
It produces fruits mandarin size, which are called mangosteen, they are the best tasting fruits in the world in many circles. The young leaves were pink. This article is based on the cultivation of a mangosteen in the Republic and the technology of its cultivation. These are not all the nutrients in mangosteen, but they have the highest concentration, so they can be considered specialized